Hidden Structure in the Study of Papuanistiecs and Melanesianology - Don Augusthinus Lamaech Flassy (Journal of Education and Vocational Research, 2017)
Development until the late 1980s and early 1990s on embodied the initiative of a typical science as the study of Papua titled Papuanistiecs as a course of study at the Department of Southeast Asia and Oceania, Faculty of Arts, University of Leiden-The Netherlands, while Melanesianology lead anthropology has been developed since 1896 when Boas carry out research works in the region of South Pacific and the Southwest Pacific. When Papuanistiecs sounds as a specific branch of the broader Melanesianology include anthropology, the course is not closed for any other specific subject areas, especially on the natural environment as physical nature (tangible) as well as the philosophy as the inner nature (intangible). A concept of intangible or philosophy of Papua-Melanesian on Socio-Cultural structure is what being proposed in this writing work as a "hidden-structureâ€ or â€˜covered structures'. The term or this formula was by the author uses to accommodate referrals various scholars who call the social structure of Papua-Melanesian as "loosely structure" or a missing structure and also as "confusing diversity" or as confuse or chaos diverse. That, "hidden structure" is said to be so because it is hidden to those outside the system which understanding as ethics while looking for people in the system who view of understanding the relationship of emics accused loose or off and confuse or confusing is very well lightly acknowledge. Melanesianology and Papuanistiecs very well coordinated by the Sydney University and the Australian National University in Canberra by enabling the University of Papua New Guinea/UPNG in Port Moresby PNG and the University of the South Pacific/USP, in Suva-Fiji. In addition to its general purpose by making Papuanistiecs and Melanesianology as a discipline of area regional study, the special purpose of the author also is about to raise these matters in connection with the State University of Cenderawasih who have declared itself as Anthropological Study Base, then the function of Papuanistiec and Melanesianology may be of the major studies take precedence in all disciplines.